Design of a modelled copepod for feeding current analysis - Ong, Wen Hao (Nanyang Technological University, 2020)
Copepods are a group of small crustaceans normally found in freshwater and saltwater habitat. They are normally around a few millimetres in length and play an important role in the marine environment as a principal link between primary production of phytoplankton and predators by influencing the bacteria distribution. This is all due to their incredible feat of influencing a huge volume of water current with their beating pattern. This beating pattern is due to the copepod moving their appendages when searching for preys.The purpose of this project is to design and analyse a copepod model. The copepod model must be able to replicate the actual copepod beating movement during feeding by using the information provided by past research. To achieve the purpose of this project, firstly, the author quantifies the copepod’s beating pattern. Secondly, the quantified beating pattern is used to design and simulate the mechanism to replicate the beating movement. Thirdly, the author has created a prototype to ensure that the mechanism is able to run smoothly. Finally, the copepod model is fabricated and tested to analyse and verify the replication of the feeding movement. The model appendages are able to follow the beating movement of the actual copepod. However, there is a slight deviation in angular displacement when compared to an actual copepod due to friction in the segment’s linkage and also dimension flaws during the fabrication. However, even with the issue, the model is able to achieve its goal of being able to replicate the actual copepod beating movement.